Genomic analysis finds no evidence of canonical eukaryotic DNA processing complexes in a free-living protist - Dayana E. Salas-Leiva; Eelco C. Tromer; Bruce A. Curtis; Jon Jerlström-Hultqvist; Martin Kolisko; Zhenzhen Yi; Joan S. Salas-Leiva; Lucie Gallot-Lavallée; Shelby K. Williams; Geert J. P. L. Kops; John M. Archibald; Alastair G. B. Simpson; et al. (Nature Communications, 2021)
The mechanisms for replicating and segregating DNA are highly conserved across eukaryotes. A comparative genomic analysis of a free-living protist finds a surprising lack of protein complexes involved in these processes, suggesting that the organism uses alternative mechanisms to process DNA.